Relationships between continuous-learning culture supervisor support, and training motivation with transfer of training : a study at a multi-level marketing company - Ho, Siew Lian (2008)
This study investigated the relationships between perception of continuous-learning culture present in organization, perceived supervisor support towards training, and training motivation with transfer of training at a multi-level marketing company in Kuching. The findings are showed positive relationships between continuous-learning culture, supervisor support, and training motivation with transfer of training. In addition, all the independents variables studied could predict transfer of training. Thus, continuous-learning culture and supervisor support (organizational contextual factors) and training motivation (individual factor) were crucial for transfer of training. Thus, in order to ensure transfer of training, HRD practitioners and managers should facilitate transfer of training by creating a continuous-learning culture in organizations, providing supervisor support to trainees and enhancing trainees’ training motivation.